SIFAT FISIK BIJI KOPI LIBERIKA - Faurina, Ulva; Inriani Br Ginting, Indah; Rasinta, Igef; Pitoyo, Sekar Utaminingtyas; Sidabalok, Dosmaria; Simanjuntak, Tresia Yuliana (Yayasan Rahmatan Fiddunya Wal Akhirah, 2026)
Indonesia is one of the world’s major coffee-producing countries, cultivating several species such as Arabica, Robusta, Liberica, and Excelsa. Among these, Liberica coffee remains less studied despite its unique morphological and physical characteristics. This research aimed to identify and analyze the physical properties of Liberica coffee beans, including their size, shape, geometric mean diameter (GMD), sphericity, bulk density, and angles of repose and friction. The study was conducted at the Biosystem Laboratory, Department of Agricultural Engineering, Faculty of Agriculture, University of Jambi, using a descriptive quantitative method. Measurements were performed using a Vernier Caliper, digital scale, and supporting instruments, with data collected from ten bean samples. The results showed that Liberica coffee beans have relatively large and elongated shapes, moderate sphericity, and good bulk density, indicating a stable structure and ease of handling during post-harvest processing. Overall, the study provides essential baseline data for developing efficient post-harvest technologies suited to the physical characteristics of Liberica coffee.